Refrigerator - Rees, Jonathan, 1966- (New York : Bloomsbury Academic, 2015)
"Object Lessons is a series of short, beautifully designed books about the hidden lives of ordinary things.Have you ever thought seriously about your refrigerator? The box humming in the background actually displays who you are and the society in which you live. This book examines the past, present, and future of the electric household refrigerator with an eye towards preventing its users from ever taking it for granted again. No mere container for cold Cokes and celery stalks, the refrigerator is actually more like a mirror-and what it reflects is chilling indeed.Object Lessons is published in partnership with an essay series in the The Atlantic"--
How refrigerators work -- How to make your refrigerator stand out -- Are the benefits of refrigeration worth the costs? -- Waste and wants -- Freezing and freezers.
Bibliografische referenties ; index
Keywords: Food -- Cooling -- Popular works; LITERARY CRITICISM / Semiotics & Theory; PHILOSOPHY / Aesthetics; Refrigeration and refrigerating machinery -- Popular works; SOCIAL SCIENCE / Anthropology / Cultural